2020
DOI: 10.1111/jfpp.14691
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin immersion affects the quality of fresh‐cut broccoli (Brassica oleraceaL.) during cold storage: Focus on the antioxidant system

Abstract: In the current study, fresh‐cut broccoli was soaked in melatonin solution before cold storage (4°C, 95% RH) for 25 days. The results indicated that 100 µM melatonin treatment inhibited the increase of L* and b* values and retained higher hue angle, total chlorophyll content, and fresh weight during storage. Furthermore, 100 µM melatonin treatment obviously increased antioxidant contents including ascorbic acid, total phenols, and flavonoids, and enhanced the antioxidant activity of florets. Individual phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Prestamo and Arroyo reported that broccoli exhibited a compact structure and a wet appearance after HPP treatment, and its pressure resistance was better than that of spinach . As we observed, the surface structure of broccoli florets was seriously damaged by 400 MPa treatment (Figure ), which might be beneficial for the extraction of antioxidant components such as ascorbic acid and phenols in broccoli florets and further enhanced the antioxidant capacity . Our results were proof of the arguments mentioned above; 200, 300, and 400 MPa treatments dramatically ( P < 0.05) enhanced the DPPH scavenging ability and ABTS value of florets (Table ), and a similar phenomenon was reported in broccoli hummus subjected to 550 MPa treatment .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Prestamo and Arroyo reported that broccoli exhibited a compact structure and a wet appearance after HPP treatment, and its pressure resistance was better than that of spinach . As we observed, the surface structure of broccoli florets was seriously damaged by 400 MPa treatment (Figure ), which might be beneficial for the extraction of antioxidant components such as ascorbic acid and phenols in broccoli florets and further enhanced the antioxidant capacity . Our results were proof of the arguments mentioned above; 200, 300, and 400 MPa treatments dramatically ( P < 0.05) enhanced the DPPH scavenging ability and ABTS value of florets (Table ), and a similar phenomenon was reported in broccoli hummus subjected to 550 MPa treatment .…”
Section: Discussionsupporting
confidence: 87%
“…We also recorded the internal temperature of each sample (Figure S6) and found that the internal temperature (65.5 °C) of 400 MPa-treated florets was higher than that of the control after MW heating at 119 W for 10 s (59.7 °C). However, as a thermally degradable component, chlorophyll seemed to degrade after MW treatment in 400 MPa-treated florets, which was often expressed as an increase in b * . The literature reported that chlorophyll in green beans and spinach degraded after HPP treatment at high temperatures, whereas the green color of green beans increased significantly after HPP treatment at room temperature .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, it was reported that 100 M melatonin treatment at the end of storage reduced the H 2 O 2 content of cut broccoli by 18% compared to the control. 31 3.4. Effect of YS on Chlorogenic Acid and Total Phenolic Content of Potatoes.…”
Section: Resultsmentioning
confidence: 99%
“…That was a good percentage. In one study, it was reported that 100 M melatonin treatment at the end of storage reduced the H 2 O 2 content of cut broccoli by 18% compared to the control …”
Section: Resultsmentioning
confidence: 99%